Respuesta :
Answer:
The value of f(2) is smaller than the value of f(1).
Step-by-step explanation:
First you plug in the numbers for x.-->f(1)=-5(1)2+2(1)+9
Then you solve this equation.-->f(1)=-5(2)+2+9 =-10+11 =1
Then you repeat both steps for f(2).-->f(2)=-5(2)2+2(2)+9 =-20+4+9 = -7
The value of f(2) is smaller than the value of f(1). Then option C is correct.
What is an expression?
Expression in maths is defined as the collection of the numbers variables and functions by using signs like addition, subtraction, multiplication and division.
The expression is solved as:-
F(x) = -5x² + 2x + 9
F ( 1 ) = -5 ( 1 )² + 2( 1 ) + 9 = -5 + 2 + 9 = 6
F ( 2 ) = -5 ( 2 )² + 2 ( 2 ) + 9= -20 + 4 + 9 = -11
Comparing the two values F( 1 ) = 6 and F (2)=-11 the value of function at x = 2 is smaller at than value of the function at x = 1.
To know more about expression follow
https://brainly.com/question/723406
#SPJ2